Pulmonary Pathogens Adapt to Immune Signaling Metabolites in the Airway - Riquelme, Sebastián A.; Wong Fok Lung, Tania; Prince, Alice (Frontiers in Immunology, 2020)
A limited number of pulmonary pathogens are able to evade normal mucosal defenses to establish acute infection and then adapt to cause chronic pneumonias. Pathogens, such as Pseudomonas aeruginosa or Staphylococcus aureus, are typically associated with infection in patients with underlying pulmonary disease or damage, such as cystic fibrosis (CF) or chronic obstructive pulmonary disease (COPD). To establish infection, bacteria express a well-defined set of so-called virulence factors that facilitate colonization and activate an immune response, gene products that have been identified in murine models. Less well-understood are the adaptive changes that occur over time in vivo, enabling the organisms to evade innate and adaptive immune clearance mechanisms. These colonizers proliferate, generating a population sufficient to provide selection for mutants, such as small colony variants and mucoid variants, that are optimized for long term infection. Such host-adapted strains have evolved in response to selective pressure such as antibiotics and the recruitment of phagocytes at sites of infection and their release of signaling metabolites (e.g., succinate). These metabolites can potentially function as substrates for bacterial growth and but also generate oxidant stress. Whole genome sequencing and quantified expression of selected genes have helped to explain how P. aeruginosa and S. aureus adapt to the presence of these metabolites over the course of in vivo infection. The serial isolation of clonally related strains from patients with cystic fibrosis has provided the opportunity to identify bacterial metabolic pathways that are altered under this immune pressure, such as the anti-oxidant glyoxylate and pentose phosphate pathways, routes contributing to the generation of biofilms. These metabolic pathways and biofilm itself enable the organisms to dissipate oxidant stress, while providing protection from phagocytosis. Stimulation of host immune signaling metabolites by these pathogens drives bacterial adaptation and promotes their persistence in the airways. The inherent metabolic flexibility of P. aeruginosa and S. aureus is a major factor in their success as pulmonary pathogens.